(untitled) (Research, Society and Development, 2022)
Information and communication technologies (ICTs) are ubiquitous in our everyday lives as well as in educational contexts, much more so after the onset of the Covid-19 pandemic. The use of ICTs in education, e.g., virtual laboratories, is of great importance to support the teaching of chemistry. Given the difficulties secondary school students encounter in understanding organic chemistry topics, this research aimed at investigating whether the use of a software program could improve teaching and promote student learning of content related to organic compounds. To this end, the data were collected by means of a pre- and a post-intervention questionnaire. The study was conducted at a public secondary school in Itacoatiara, AM, Brazil, with 3rd-year (final year) students. The software programs IrYdium Chemistry Lab, LAPEQ-USP (Laboratory of Research in Chemistry Teaching and Educational Technologies, University of São Paulo), and Simulations for Chemistry were employed to introduce the participating students to a chemistry lab and to simulate lab practices involving chromatography experiments. The analysis of the collected data suggests that the use of virtual labs promoted the participants’ motivation to learn organic chemistry as well as ability to integrate concepts taught in the classroom to aspects of their everyday lives. The participating students also reported that they would like to use other virtual lab programs to study chemistry, thus constituting new ways of learning beyond the classroom.